CRISPR/Cas9-Mediated Genome Editing of Soluble Starch Synthesis Enzyme in Rice for Low Glycemic Index - Mohd Rizwan Jameel; Zubaida Ansari; Asma A. Al-Huqail; Sheeba Naaz; Mohammad Irfan Qureshi (Agronomy, 2022)
In the present study, the selected rice (Oryza sativa cv. indica) was genetically modified to increase the amylose content in the seeds. The ‘CRISPR-Cas9’ genome-editing tool was used to knock out three isoforms of soluble starch synthase (SSS) viz. SSSII-1, SSSII-2 and SSSII-3. A genetic transformation vector designed with appropriate gRNAs, Cas9, and antibiotic resistance was used to create SSS knockout mutants to enrich the content of amylose. Putative rice mutants were developed with high amylose content in the seeds of up to 63% as compared to 23% in the wild types (control). Rice with a low Glycemic Index (GI) value and high amylose content rice is preferred to avoid a sudden rise in glucose in the bloodstream. The frequencies of bi-allelic or homozygous transgenic lines of SSSII-1, SSSII-2, and SSSII-3 in the first generation were tested via the Mendelian fashion of segregated bi-allelic lines in the T1 generation of the putative rice mutants. The T1 generation segregation showed a frame-shift mutation. A molecular characterization of the putative mutants successfully demonstrated the development of a Cas9-free rice mutant with a higher amount of amylose in the rice.